Ulcérations périnéales révélant une maladie de Crohn - Agharbi, Fatima-Zahra (Pan Afr Med J, 2019)
The whole of the lesions associated with Crohn's disease affecting the anal canal, the skin of the perineum, the bottom-rectum and the recto vaginal septum are referred to as anoperineal lesions of Crohn's disease. The main types of primary lesions include ulcerations, suppurations and stenoses. Crohn's disease-like anoperineal lesions are often suspected in patients with severe inflammatory process, peri-anal skin thickening, œdematous marisques, multiple lesions and lesions extending above pectineal line. Fistulas usually originate from an ulceration or a scar rather than the crypts of the anal canal. Elementary lesions of Crohn's disease are rarely isolated and they are, in most cases, combined lesions. The presence of a stenosis of the anal canal or of the rectum is very often associated with an inflammatory and suppurative process. Anal ulcerations are complicated with suppuration in half of the cases. We report the case of 45-year old woman treated for autoimmune thyroiditis and vitiligo who presented with knife-cut painful perineal ulcerations. The patient reported episodes of diarrhea during interview. Histological examination of skin lesions showed epitheliogigantocellular granuloma without caseous necrosis and digestive exploration suggested Crohn's disease which was confirmed with histology.